Unique skin nodules following COVID-19 vaccination: a case report of cutaneous plasmacytosis and review of the literature - Xiaoxi Xu; Wuwu Ding; Haizhen Song; Dong Wang (Virology Journal)
Abstract Background Cutaneous plasmacytosis (CP) is a rare disorder that may affect two or more organ systems, such as skin, lymph nodes or lungs. The pathogenesis of CP remains unknown, and in most cases, the condition follows a chronic and benign clinical course without spontaneous remission. Case presentation A 50-year-old male who developed necrotizing skin nodules without other systemic abnormalities four days after the first doses of the Coronavirus disease 2019 (COVID-19) vaccination. Oral prednisone improved the lesions by approximately 70%. However, signs of CP recurrence manifested 15 days after the second dose of COVID-19 vaccination. Ultimately, the patient experienced spontaneous remission after contracting SARS-CoV-2 infection. Conclusion This case uniquely associates COVID-19 inactivated vaccine with CP, where the same lesions appeared after two vaccinations and subsequently resolved following SARS-CoV-2 infection. This provides valuable clinical data for future studies on viral infections and cutaneous B-cell immunity.